2023
DOI: 10.1038/s41598-023-28449-8
|View full text |Cite
|
Sign up to set email alerts
|

Serum cortisol and insulin-like growth factor 1 levels in major depressive disorder and schizophrenia

Abstract: The pathophysiology underlying major depressive disorder (MDD) and schizophrenia is related to endocrine system functions and includes changes in the blood levels of cortisol and insulin-like growth factor 1 (IGF-1). However, these hormones have not been investigated simultaneously in patients with MDD and schizophrenia. We investigated the differences in serum cortisol and IGF-1 levels among patients with MDD and schizophrenia and controls. We included 129 patients with MDD, 71 patients with schizophrenia, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
3

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 64 publications
(195 reference statements)
0
7
3
Order By: Relevance
“…In some studies, IGF-1 peripheral levels were found to be significantly increased in depression [38][39][40]43,44,49] regardless of ethnicity, since some works were done in Europe [38][39][40]43], North America [44] and Japan [49]. What is more, IGF-1 was found upregulated either when patients were following AD treatments [40,43,49] or not [38,39,44] by the time protein measurements were taken. This may suggest that the levels of IGF-1 might be increased in depression regardless of treatment conditions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In some studies, IGF-1 peripheral levels were found to be significantly increased in depression [38][39][40]43,44,49] regardless of ethnicity, since some works were done in Europe [38][39][40]43], North America [44] and Japan [49]. What is more, IGF-1 was found upregulated either when patients were following AD treatments [40,43,49] or not [38,39,44] by the time protein measurements were taken. This may suggest that the levels of IGF-1 might be increased in depression regardless of treatment conditions.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, this is the first time that IGF-2, IGFBP-5 and IGFBP-7 plasma protein levels have been addressed in depressed patients. On the contrary, in the last few decades, IGF-1 has received far more attention than IGF-2 in the context of depression [38][39][40][41][42][43][44][45][46][47][48][49]. In some studies, IGF-1 peripheral levels were found to be significantly increased in depression [38][39][40]43,44,49] regardless of ethnicity, since some works were done in Europe [38][39][40]43], North America [44] and Japan [49].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Obesity activates mTORC1 in microglia and astrocytes with disabled autophagy, while rapamycin treatment restores autophagy and reduces depressive and anxiety-like behaviors [ 134 ]. Autophagy inhibition caused by obesity might explain the link between excessive adiposity and ASD, MDD or SCZ [ 135 , 136 ], but the observations suggesting that fasting may improve MDD must be replicated in large randomized studies [ 137 ]. These findings suggest that mTORC1 is hyperactivated in neuropsychiatric diseases, but there are exceptions to this rule.…”
Section: Hallmark 3: Recycling and Turnovermentioning
confidence: 99%